Predicting the Occurrence of Financial Reporting Fraud: S.C.C.O.R.E. Model Approach - Nico Alexander; Ade Hanifa Putri; Ariesta Tika Kinanti Pangestu Sulistyo Putri (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
This research was carried out to gather empirical evidence regarding the factors that affect financial reporting fraud, utilizing the S.C.C.O.R.E theory approach, also known as the Hexagon theory. Those factors include stimulus (financial stability and external pressure), capability (director changes), collusion (related party transactions), opportunity (ineffective monitoring and nature of industry), rationalization (auditor changes), and ego (political connection). The research analyzed 130 companies listed on the Indonesia Stock Exchange, focusing on both cyclicals and non-cyclicals sectors, which were selected through a purposive sampling technique. This research employed a logistic linear regression. The findings indicated that the factor influencing financial reporting fraud is the stimulus provided by financial stability. The management's inclination to preserve a stable financial condition and avoid any financial downturn motivates them to engage in fraudulent activities. Consequently, the stronger the management's desire to uphold the company's financial stability, the greater the likelihood of fraud occurring. Furthermore, this research shows that external pressure, director changes, related party transactions, ineffective monitoring, the nature of industry, auditor changes, and political connections do not affect financial reporting fraud.